Zeolite supported bimetallic catalyst system: The effect of metal loading for catalytic pyrolysis of jatropha residue - Goodwin, V. (Trans Tech Publications Ltd, 2017)
Two transition metals were loaded on H-ZSM-5 zeolite to produce bimetallic zeolite supported catalysts for catalytic pyrolysis reaction. Ni and Co metal were loaded on H-ZSM-5 via wet impregnation method. The loading sequence was applied using one-step and two-step loading method. The different loading sequence affect surface properties of catalyst and catalytic activity in pyrolysis reaction. The bimetallic catalysts were prepared at Ni+Co metal loading content of 10+ 10 wt (Ni:Co=1:1) to 10+20 wt (Ni:Co=1:2 or 2:1). All bimetallic catalysts supported on H-ZSM-5 were calcined and characterized by X-ray Diffraction (XRD), Surface area analysis (BET) and Temperature Programmed Desorption of ammonia (NH3-TPD). The XRD patterns of bimetallic zeolite supported catalysts revealed that loading of two metals at high content affect crystalline structural of ZSM-5 support. All XRD patterns illustrated peaks characteristic of ZSM-5, cobalt oxide and nickel oxide. The NH3-TPD results showed number of acid sites of the catalyst which revealed that the acid sites of ZSM-5 support was weakened with transition metal added. The twostep loading of 10+20 wt metals on ZSM-5 reduced the peak intensities of NH3 desorption due to the metal particles aggregate on acid sites of ZSM-5. The two-step 10+20 wt bimetallic catalysts has the lowest surface acidity, followed by the one-step 10+20 wt, the two-step 10+10 wt and the one-step 10+10 wt bimetallic catalysts, respectively. Jatropha residue was used for catalytic pyrolysis study. Jatropha residue and bimetallic catalyst was pyrolyzed at 500 °C in a pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). The product vapor was analyzed by GC/MS for the different groups of organic products such as fatty acid, aldehydes, ketones, aliphatic hydrocarbons, aromatic hydrocarbons and nitrogen compounds. The product from catalytic pyrolysis of jatropha residue with bimetallic zeolite supported catalysts enhance deoxygenation reaction that resulted in high aliphatic and aromatic hydrocarbons product. The one-step loading at ratio Ni:Co = 1:1 (10+10 wt) gave the highest hydrocarbons product yield at 57.81. © 2017 Trans Tech Publications, Switzerland.